High Heating Rates Affect Greatly the Inactivation Rate of Escherichia coli - Huertas, Juan-Pablo; Aznar, Arantxa; Esnoz, Arturo; Fernández, Pablo S.; Iguaz, Asunción; Periago, Paula M.; Palop, Alfredo (Frontiers in Microbiology, 2016)
Heat resistance of microorganisms can be affected by different influencing factors. Although the effect of heating rates has been scarcely explored by the scientific community, recent researches have unraveled its important effect on the thermal resistance of different species of vegetative bacteria. Typically heating rates described in the literature ranged from 1 to 20ºC/min but the impact of much higher heating rates is unclear. The aim of this research was to explore the effect of different heating rates, such as those currently achieved in the heat exchangers used in the food industry, on the heat resistance of Escherichia coli. A pilot plant tubular heat exchanger and a thermoresistometer Mastia were used for this purpose. Results showed that fast heating rates had a deep impact on the thermal resistance of E. coli. Heating rates between 20 and 50ºC/min were achieved in the heat exchanger, which were much slower than those around 20ºC/s achieved in the thermoresistometer. In all cases, these high heating rates led to higher inactivation than expected: in the heat exchanger, for all the experiments performed, when the observed inactivation had reached about seven log cycles, the predictions estimates about 1 log cycle of inactivation; in the thermoresistometer these differences between observed and predicted values were even more than ten times higher, from 4.07 log cycles observed to 0.34 predicted at a flow rate of 70 mL/min and a maximum heating rate of 14.7ºC/s. A quantification of the impact of the heating rates on the level of inactivation achieved was established. These results point out the important effect that the heating rate has on the thermal resistance of E. coli, with high heating rates resulting in an additional sensitization to heat and therefore an effective food safety strategy in terms of food processing.